Tafsir dan Hadits Mengenai Riba - Hilda Olyvia Wulandari; Nabila Rahma Febrianty; Naila Baraty; Ririn Tri Wahyuni; Silvia Dwi Rahmawati; Qurrata A’yunin; Taufiq Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Based on the Qur'an and Hadith, this study investigates how Islamic teachings prohibit usury. Usury is an economic practice that damages the financial system. This study aims to provide an explanation of the meaning, legal status, and interpretation of the verses of the Qur'an and Hadith related to usury. This study analyzes the concept of usury and its types in contemporary financial transactions using a qualitative descriptive approach and literature study. The results of the study indicate that many communities, including Islamic communities, still do not understand the meaning of usury and its effects. Consequently, comprehensive education is essential to eliminate usury and support the development of a just and sustainable Islamic economic system.